Preventing depression using a smartphone app: a randomized controlled trial. Issue 3 (6th February 2022) - Deady, Mark; Glozier, Nicholas; Calvo, Rafael; Johnston, David; Mackinnon, Andrew; Milne, David; Choi, Isabella; Gayed, Aimee; Peters, Dorian; Bryant, Richard; Christensen, Helen; Harvey, Samuel B.
Abstract: Background: There is evidence that depression can be prevented; however, traditional approaches face significant scalability issues. Digital technologies provide a potential solution, although this has not been adequately tested. The aim of this study was to evaluate the effectiveness of a new smartphone app designed to reduce depression symptoms and subsequent incident depression amongst a large group of Australian workers. Methods: A randomized controlled trial was conducted with follow-up assessments at 5 weeks and 3 and 12 months post-baseline. Participants were employed Australians reporting no clinically significant depression. The intervention group ( N = 1128) was allocated to use HeadGear, a smartphone app which included a 30-day behavioural activation and mindfulness intervention. The attention-control group ( N = 1143) used an app which included a 30-day mood monitoring component. The primary outcome was the level of depressive symptomatology (PHQ-9) at 3-month follow-up. Analyses were conducted within an intention-to-treat framework using mixed modelling. Results: Those assigned to the HeadGear arm had fewer depressive symptoms over the course of the trial compared to those assigned to the control ( F 3, 734.7 = 2.98, p = 0.031). Prevalence of depression over the 12-month period was 8.0% and 3.5% for controls and HeadGear recipients, respectively, with odds of depression caseness amongst the intervention group of 0.43 ( p = 0.001, 95% CI 0.26–0.70). Conclusions: This trial demonstrates that a smartphone app can reduce depression symptoms and potentially prevent incident depression caseness and such interventions may have a role in improving working population mental health. Some caution in interpretation is needed regarding the clinical significance due to small effect size and trial attrition. Trial Registration Australian and New Zealand Clinical Trials Registry (www.anzctr.org.au/ ) ACTRN12617000548336